Spontaneous Pregnancy in Primary Amenorrhea; a Case Report - Das, Ananya; Borah, Tulon; Panda, Subrat (Journal of Reproduction & Infertility, 2010)
Introduction: Primary ovarian failure (POF) is a syndrome composed of amenorrhea, estrogen deficiency and Follicular Stimulating Hormone (FSH) of menopausal ranges in young women. In this article, we report a case of primary amenorrhea that presented with full term pregnancy.Case Presentation: A 29-year old woman with a history of primary amenorrhea attended hospital with full term pregnancy. She had experienced a few episodes of withdrawal bleeding on hormonal treatment initially and she had conceived spontaneously. Subsequently, she had uneventful pregnancy and caesarean delivery on maternal request. Conclusion: This case was presented to emphasize the real chances of spontaneous conceptions due to intermittent and unpredictable ovarian function in patients with POI. Nevertheless, egg donation is still considered the best option for infertility in such women.
Keywords: Estrogen deficiency; Follicular stimulating hormone; Pregnancy; Primary amenorrhea; Primary ovarian insufficiency